Zhongyong thinking (doctrine of the mean) and internet addiction: The mediation of maladaptive cognition and the moderation of subject - Wei, Hua; Xu, Hemuqing; Chen, Wu; Lu, Lijun (Frontiers in Public Health, 2023)
Based on the cognitive-behavioral model of pathological internet use, this study explored the relationship between zhongyong thinking (doctrine of the mean) and internet addiction, and examined the mediation of maladaptive cognition and the moderation of subject. Convenience sampling was used to select 1,518 college students for the questionnaire. The participants were 15–26 years old (M = 19.77; SD = 1.45), including 776 male and 742 female students. The results showed that zhongyong thinking was significantly negatively correlated with maladaptive cognition (r = −0.19, p < 0.001) and internet addiction (r = −0.14, p < 0.001). Maladaptive cognition was significantly positively correlated with internet addiction (r = 0.46, p < 0.001). After controlling for age, gender, zhongyong thinking negatively predicted internet addiction (B = −0.06, p < 0.05), maladaptive cognition positively predicted Internet addiction (B = 0.45, p < 0.001). Zhongyong thinking negatively predicted maladaptive cognition (B = −0.19, p < 0.001). Moreover, the bias-corrected bootstrapping mediation test indicated that the process by which zhongyong thinking predicted Internet addiction through maladaptive cognition was significant, indirect effect = −0.08, SE = 0.01, 95% CI = [−0.11, −0.06]. Subject has no moderating effect on the relationship between zhongyong thinking and maladaptive cognition. The interaction between zhongyong thinking and subject was not a significant predictor of maladaptive cognition (B = 0.05, p > 0. 05). The present results suggest that zhongyong thinking as a traditional Chinese wisdom can still play an important role in regulating young people's behavior in the digital age.